The Rx transcription factor is required for determination of the retinal lineage and regulates the timing of neuronal differentiation - Yamamoto, Maho; Ong, Agnes Lee Chen ; 0000-0002-2925-6638; Shinozuka, Takuma; Sasai, Noriaki (Development Growth and Differentiation, 2022)
Understanding the molecular mechanisms leading to retinal development is of great interest for both basic scientific and clinical applications. Several signaling molecules and transcription factors involved in retinal development have been isolated and analyzed; however, determining the direct impact of the loss of a specific molecule is problematic, due to difficulties in identifying the corresponding cellular lineages in different individuals. Here, we conducted genome-wide expression analysis with embryonic stem (ES) cells devoid of the Rx gene, which encodes one of several homeobox transcription factors essential for retinal development. We performed three-dimensional differentiation of wild-type and mutant cells and compared their gene-expression profiles. The mutant tissue failed to differentiate into the retinal lineage and exhibited precocious expression of genes characteristic of neuronal cells. Together, these results suggest that Rx expression is an important biomarker of the retinal lineage and that it helps regulates appropriate differentiation stages.
Publisher Copyright: © 2022 Japanese Society of Developmental Biologists.
Keywords: CRISPR/Cas9; embryonic stem cells; high-throughput expression profiling; organoid; retina